Regional and national identity examinations on the Slovenian settlements of historical guardsmen’s land - Balogh, András; Kardos, Laura (Journal for Geography, 2019)
Our study focuses on the research of regional and national identity – it is mainly based on empirical survey realised with questionnaires - in the border regions of Slovenia, in the former part of the Guardsmen’s Land, still inhabited by Hungarians. These settlements are: Hodoš (Őrihodos), Krplivnik (Kapornak) and Domanjševci (Domonkosfa). To compile the required sample, we started out from the census data and from the information of the local self-governments. In addition to the identity examination as the primary research target, the questionnaire allowed as an additional result the drawing up of the exact ethnic spatial structure of the researched settlements, which is also described.